Regional aspects of availability of expectorants and antitussive drugs - V. М. Timiryanova; А. V. Samorodov; Z. А. Valiullina; V. B. Prudnikov; D. Kh. Krasnoselskaya (Фармакоэкономика, 2025)
Background. In the Russian Federation (RF), the problems of supplying the population with medicines are associated with both their physical and economic accessibility, which are heavily dependent on such various external shocks as pandemic, special military operation and other ones. There is a regional differentiation in the availability of individual drugs and their price levels, which determines the variability of market responses to external shocks and government-developed mechanisms for stabilizing markets.Objective: to reveal regional availability dependencies of antitussive drugs and expectorants.Material and methods. The study was carried out using data from the online retail sales analytics service in the RF, which forms a database based on cash receipts containing information on the sales price of 55 drugs for the period from January 1, 2021 until December 31, 2023 in the context of 83 RF constituent entities. Analysis included assessment of the structure of medicines sold by their composition, place of production, inclusion in the list of vital and essential drugs, as well as dynamics, variations and spatial autocorrelation of prices, availability of medicines in the regions of RF.Results. Range availability increased for 35 out of 55 drugs under review while all of them in 2023 were represented only in 5 RF constituent entities. Prices were characterized by high variation both in trade names (TNs) and RF constituent entities, varying from 13% (Doktor MOM®) to 181% (Kuka). The dynamics of prices for domestic and foreign produced drugs until 2022 and after this timepoint differed. The economic availability of medicines in terms of TNs and RF constituent entities was in a very wide range (from 0.003 to 1.4 daily median income). These differences were not chaotic, but spatially dependent: positive spatial autocorrelation of prices was established.Conclusion. The analysis revealed different economic accessibility and range availability of drugs in regions where external shocks have a significant influence on their dynamics. At the same time, we observed the variability of the restoration rate of spatial equilibrium of drug markets in terms of TNs, that should be considered when designing stabilization activities.